Establishment of six homozygous MHC-B haplotype populations associated with susceptibility to Marek’s disease in Chinese specific pathogen-free BWEL chickens - Caixia Gao; Lingxia Han; Han Jianlin; Jiasen Liu; Qian Jiang; Dongchun Guo; Liandong Qu (Elsevier, 2015)
The highly polymorphic chicken major histocompatibility complex (MHC) is associated with different levels of immunologic responses to certain avian pathogens. MHC-B haplotype chickens are an important genetic resource for studying the genetic determination of pathogen resistance and susceptibility. The BWEL chicken population is the only specific pathogen-free (SPF) chickens bred and developed by the State Center of Poultry Genetic Resources of Laboratory Animals in China. In this study, we successfully established six homozygous MHC-B haplotype populations from the BWEL chickens using microsatellite marker technology, named as BW/G(1, 2, 3, 5, 6, 7) lines, and their molecular genotypes were matched to six serologically defined MHC-B haplotypes, B13, B15, B2, B5, B21 and B19, respectively. The sequences of BF genes exons 2 and 3 from four successive generations (F1–F4) of the BW/G(n) lines were completely consistent with those of serologically defined MHC-B haplotypes. Subsequently, six BW/G(n) line specific allo-antisera were prepared by immunization with red blood cells (RBCs) and hemagglutination tests results showed the BW/G(n) SPF chickens could be serologically differentiated. Additionally, susceptibility to Marek’s disease (MD) in the BW/G3 (B2 haplotype) and BW/G7 (B19 haplotype) lines were determined by comparing mortality, macroscopic and histopathological lesions, and viral loads in feather pulp. The BW/G7 line showed greater genetic susceptibility to the very virulent MD virus (MDV) strain than the BW/G3 line. The establishment of MHC-B haplotype chicken populations associated with susceptibility to MD will be helpful for studying host immune responses and further developing the more effective vaccines in the context of MHC specificities, and they are also very useful for an understanding of MHC genes architecture and function.